Electronic Learning Media on Chemical Bonding Materials: A Literature Study - Ramadani, Mutipa; Guspatni, Guspatni (Journal of Educational Sciences, 2025)
Chemical bonding is a basic material that helps students to understand other chemical concepts, because it provides a basic explanation of the process of a reaction. chemical bonding material becomes material that is considered difficult by students because of its abstract concept. Learning media is needed in the learning process, to be able to improve students' understanding, skills, learning outcomes, achievement and motivation to learn. The purpose of this study is to determine the electronic learning media that have been developed and used on chemical bonding materials. This study used of the literature review method from several articles in the research database based on the validity, practicality, and effectiveness values, then analyzed and concluded. The results of this study found 27 electronic learning media in the form of Web site, Electronic Module, Electronic teaching materials, Electronic Learning, Comics, Electronic Book, Video, Audio Visual, Ludo, Animation, Khoot, Computational Chemistry and Power-Point.